Teach your browser new tricks. - Berenstain, Adam (Mac life)
Your web browser can Google, it can YouTube, and it can even Tweeter, but if that's all you're doing with it, you haven't scratched the surface of its potential. A universe of extensions and bookmarlets is out there, and these free software add-ons give your browser the power to remove add, reshuffle web pages to your liking, speed up your downloads, rip videos, and perform other wizardly feats. You can even get into the act with Mobile Safari on your iPhone, iPad, or iPod touch. Whether you're just starting out (if so, check out our beginner's guide on p36) or you're already armed with a suite of your favorite extensions, our guide to the best browser add-ons will transform your time surfing. It'll practically feel like magic.